Current practice of allergy diagnosis and the potential impact of regulation in Europe - Cardona, Victoria; Pfaar, Oliver (Allergy, 2018)
In the European Union (EU), the regulatory framework regarding diagnostic allergen extracts is currently in the process of being implemented at the national level. Due to these regulations, the initial and periodic renewal expenses for the registration of diagnostic allergen extracts may render extract production unprofitable. Consequently, many extracts may be at risk of removal from the market. The current survey, which was conducted by a task force of the European Academy of Allergy and Clinical Immunology, aimed to assess the current practice of allergy diagnosis in Europe. This survey revealed that skin tests continue to be the main diagnostic procedure and are used as the first option in almost two-third of all types of allergic diseases and in 90% of individuals suffering from respiratory allergies. Therefore, there is a need to ensure the availability of high-quality allergen extracts to maintain the common diagnostic procedures used by EU professionals. To reach this goal, it is necessary to align efforts and establish active partnerships between manufacturers, relevant scientific societies, consumer organizations and authorities to maintain the availability of these diagnostic tools.